A Systematic Review of the Effectiveness of Tongue Lip Adhesion in Improving Airway Obstruction in Children With Pierre Robin Sequence. Issue 6 (September 2016) - Viezel-Mathieu, Alex; Safran, Tyler; Gilardino, Mirko S.
Abstract : Background: Tongue–lip adhesion (TLA) involves surgically tethering the tongue forward to the lower lip and is a technique to relieve airway obstruction caused by glossoptosis and retrognathia. The purpose of the present study was to evaluate the effectiveness of TLA for the treatment of airway compromise in patients with Pierre Robin sequence (PRS). Methods: A comprehensive literature review was performed. Inclusion criteria consisted of patients having undergone isolated tongue lip adhesion and results that included airway outcome. Selected manuscripts were analyzed with regards to patient demographics, principle diagnosis, pre and postintervention airway status, and complications. Results: Thirteen manuscripts met inclusion criteria, yielding 268 patients with PRS who underwent TLA. The mean age at the time of procedure was 30.5 days. Tongue lip adhesion proved to be successful in relieving airway obstruction caused by PRS in 81.3% (n = 218) of patients. Nonsyndromic patients benefited from a higher success rate as compared with the syndromic cohort (91.5% and 79.8% respectively, P  = 0.0361). Eight patients who were initially successfully managed with TLA required a repeat procedure due to dehiscence. Conclusions: Tongue–lip adhesion is a safe and effective technique and is associated with lower morbidity and mortality as compared with mandibular distraction osteogenesis and tracheostomy and should be considered in patients with PRS who fail conservative management. The greater success and lower complication rates in nonsyndromic patients reinforce the importance of proper patient selection and consideration of other techniques such as mandibular distraction osteogenesis should be given in patients with associated syndromic diagnoses.